Ekstrak air Kayumanis (Cinnamomum burmanii) Menurunkan Tingkat Serum INOS Tikus Wistar Diabetes. - Alfania Novita Putri Perdana; Doti Wahyuningsih; Yudi Purnomo (Published by Faculty of Medicine Universitas Islam Malang, 2017)
Backgound. iNOS enzyme was secreted by immunocompetent cells during pathogenesis of diseases involving inflammation. The enzyme catalized a reaction resulting in nitric oxide radical (NO˙) in large amount. The radical reacts with superoxide (O2 ̅ ) to yield peroxynitrite ( ONOO ̅ ) which are highly reactive and toxic to the tissues. Kayumanis (C.burmanii) was considered rich with compounds overcoming iNOS secretion. This is the initial study of kayumanis potency in reducing iNOS expression. Diabetes is one of many diseases with high level of serum iNOS and was choosen for the study.Purpose. To study kayumanis potency in reducing serum iNOS of a diabetic conditions.Methode.5 groups of rats, each 5, four groups of which were intraperitoneally injected by aloxan at dose of 150 mg/Kg BW to induce hyperglycemia. The another group recieved no treatment. Three groups of diabetic rats were treated with C. Burmanii each day at dose of 0. 5 ml, 1 ml, and 2 ml respectively for 14 days. The remained diabetic group was untreated. Serum iNOS were measured by ELISA. iNOS data were statistically analyzed using ANOVA followed by LSD test (p ≤ 0.05).Results. C.burmanii dose of 1 ml reduced serum iNOS of diabetic rats (p ≤ 0.05). The two other doses of C.burmanii did not reduced the enzyme (p ≥ 0.05).Conclusion. C. Burmanii may have potention of reducing iNOS serum in diabetic condition.Key words: iNOS;Cinnamomum burmanii; diabetes; aloxan